PENINGKATAN MINAT BELI KONSUMEN DI TOKO ROBERTO SUMBAWA BESAR MELALUI ASPEK HARGA DAN PROMOSI - A Asmini; K Kamaruddin; Eka Putri Maulani (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of price on buying interest at Toko Roberto Sumbawa. The type of research used is associative research. The type of data used is quantitative data obtained directly from research respondents using a questionnaire as a research instrument. The population in this research is the consumers of Toko Roberto Sumbawa Besar whose number is not known with certainty. Considering that the number of population in this study is not known with certainty, the sampling was carried out using the Paul Leddy formula so that a total of 96 respondents were obtained according to the calculation results. Data analysis was performed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determination coefficient test (R2). Based on the results of the data analysis that has been done, it shows that prices and promotions have a positive and significant effect on consumer buying interest at Roberto Sumbawa Besar Stores, both partially and simultaneously. The degree of influence of price and promotion on consumer buying interest at the Roberto Sumbawa Besar Store is 23.1%, while the remaining 76.9% is influenced by other variables not examined in this study, such as service quality, product quality and brand image.